Experimental study on electric corrosion damage of bearing and solution. (October 2022) - Huan, Jie; Li, Songhua; Xia, Zhongxian; Wang, Yonghua; Wang, Weinan; Shi, Guangda
During the operation of the bearing in the motor, the induced current will inevitably be generated. The bearing raceway will be damaged by current. In this paper, the oil film thickness and capacitance in the bearing are analyzed in detail, and the relationship between oil film thickness, rotational speed, and load is obtained. The oil film thickness increases with the increase of bearing rotation speed and decreases slightly with the increase of load. The minimum oil film thickness of the bearing is between 0.4 μm and 2.9 μm. The capacitance of bearing is influenced by Hertz contact area, oil film thickness, and lubricant quality. It is between 1.9 pF and 34.7 pF. A shaft current test rig was developed. Based on the analysis results, orthogonal tests are set up to study the influence of voltage, rotation speed, and load on bearing operation. By using range analysis and variance analysis, the same conclusion is obtained: the most dominant factors affecting the raceway damage width, surface roughness, and vibration amplitude are voltage, load, and rotation speed, respectively. The mixed ceramic bearing and full-ceramic bearing are used instead of steel bearing to solve the problem of shaft current. Add conductive grease and non-conductive grease, respectively, and analyze and compare the advantages and disadvantages of different combinations from the perspective of temperature and friction and wear. The order from inferior to superior is steel bearing, hybrid ceramic bearing with ceramic outer ring, hybrid ceramic bearing with ceramic inner ring, hybrid ceramic bearing with ceramic ball and full-ceramic bearing. By using non-conductive grease, the damage is reduced by 16%–29%, surface roughness is reduced by 90%–122%, and vibration is reduced by 23%–176%. Under the same conditions, the bearings using non-conductive grease are better than those using conductive grease.